Asynchronously bounded filtering for discrete-time switched positive systems. (May 2022) - Shi, Shuang; Fei, Zhongyang; Dai, Ming-Zhe
Abstract: In this paper, the asynchronous ℓ 1 filtering issue is investigated for a class of discrete-time switched positive systems. An improved semi-time-dependent framework is established, which is compatible with the switching feature of asynchronously switched systems. First of all, the stability and ℓ 1 -gain analysis for switched positive linear systems are studied by using a semi-time-dependent multiple copositive Lyapunov function. On this foundation, both upper-bound and lower-bound positive filters are designed, which can ensure the positivity, stability and non-weighted ℓ 1 -gain of the corresponding filtering error systems. Moreover, the developed bounded filtering scheme is semi-time-dependent, which can achieve less conservative performance compared with the conventional time-independent methodology. Finally, an example is provided to demonstrate the potentials and merits of the proposed filtering scheme.